Efficacy of the MAGE-A3 cancer immunotherapeutic as adjuvant therapy in patients with resected MAGE-A3-positive non-small-cell lung cancer (MAGRIT): a randomised, double-blind, placebo-controlled, phase 3 trial. Issue 6 (June 2016) - Vansteenkiste, Johan F; Cho, Byoung Chul; Vanakesa, Tonu; De Pas, Tommaso; Zielinski, Marcin; Kim, Moon Soo; Jassem, Jacek; Yoshimura, Masahiro; Dahabreh, Jubrail; Nakayama, Haruhiku; Havel, Libor; Kondo, Haruhiko; et al.
Summary: Background: Fewer than half of the patients with completely resected non-small-cell lung cancer (NSCLC) are cured. Since the introduction of adjuvant chemotherapy in 2004, no substantial progress has been made in adjuvant treatment. We aimed to assess the efficacy of the MAGE-A3 cancer immunotherapeutic in surgically resected NSCLC. Methods: In this randomised, double-blind, placebo-controlled trial, we recruited patients aged at least 18 years with completely resected stage IB, II, and IIIA MAGE-A3-positive NSCLC who did or did not receive adjuvant chemotherapy from 443 centres in 34 countries (Europe, the Americas, and Asia Pacific). Patients were randomly assigned (2:1) to receive 13 intramuscular injections of recMAGE-A3 with AS15 immunostimulant (MAGE-A3 immunotherapeutic) or placebo during 27 months. Randomisation and treatment allocation at the investigator site was done centrally via internet with stratification for chemotherapy versus no chemotherapy. Participants, investigators, and those assessing outcomes were masked to group assignment. A minimisation algorithm accounted for the number of chemotherapy cycles received, disease stage, lymph node sampling procedure, performance status score, and lifetime smoking status. The primary endpoint was broken up into three co-primary objectives: disease-free survival in the overall population, the no-chemotherapy population, and patients with a potentially predictive gene signature. The final analyses included the total treated population (all patients who had received at least one treatment dose). This trial is registered with ClinicalTrials.gov, number NCT00480025 . Findings: Between Oct 18, 2007, and July 17, 2012, we screened 13 849 patients for MAGE-A3 expression; 12 820 had a valid sample and of these, 4210 (33%) had a MAGE-A3-positive tumour. 2312 of these patients met all eligibility criteria and were randomly assigned to treatment: 1515 received MAGE-A3 and 757 received placebo and 40 were randomly assigned but never started treatment. 784 patients in the MAGE-A3 group also received chemotherapy, as did 392 in the placebo group. Median follow-up was 38·1 months (IQR 27·9–48·4) in the MAGE-A3 group and 39·5 months (27·9–50·4) in the placebo group. In the overall population, median disease-free survival was 60·5 months (95% CI 57·2–not reached) for the MAGE-A3 immunotherapeutic group and 57·9 months (55·7–not reached) for the placebo group (hazard ratio [HR] 1·02, 95% CI 0·89–1·18; p=0·74). Of the patients who did not receive chemotherapy, median disease-free survival was 58·0 months (95% CI 56·6–not reached) in those in the MAGE-A3 group and 56·9 months (44·4–not reached) in the placebo group (HR 0·97, 95% CI 0·80–1·18; p=0·76). Because of the absence of treatment effect, we could not identify a gene signature predictive of clinical benefit to MAGE-A3 immunotherapeutic. The frequency of grade 3 or worse adverse events was similar between treatment groups (246 [16%] of 1515 patients in the MAGE-A3 group and 122 [16%] of 757 in the placebo group). The most frequently reported grade 3 or higher adverse events were infections and infestations (37 [2%] in the MAGE-A3 group and 19 [3%] in the placebo group), vascular disorders (30 [2%] vs 17 [3%]), and neoplasm (benign, malignant, and unspecified (29 [2%] vs 16 [2%]). Interpretation: Adjuvant treatment with the MAGE-A3 immunotherapeutic did not increase disease-free survival compared with placebo in patients with MAGE-A3-positive surgically resected NSCLC. Based on our results, further development of the MAGE-A3 immunotherapeutic for use in NSCLC has been stopped. Funding: GlaxoSmithKline Biologicals SA.